Analisis Permasalahan Pengurusan Izin Mendirikan Bangunan di Kota Bekasi (Kantor Pelayanan Terpadu Satu Pintu Kecamatan Bekasi Selatan Kota Bekasi) - Margareta, Elvina Rosa; Samudra, Azhari; Nazriah, Ainun (FIA Unkris Press, 2023)
Building Construction Permit or often referred to as IMB is a permit granted by the Regional Head to building owners who change forms, build new buildings, renovate and maintain their houses. In the City of Bekasi, the implementation of a Building Permit is regulated in Regional Regulation No. 04 of 2017 concerning the disciplinary order and IMB retribution. The results of this study are expected to be input for the South Bekasi District in order to create the first IMB management. This research uses the theory of Public Service Quality according to Sinambela which has indicators of Transparency, Accountability, Conditional, Participation, Equality of Rights, Balance of Rights and Obligations. This study uses a descriptive qualitative approach. The results of this study indicate that the quality of obtaining a Building Permit in the South Bekasi District is in accordance with the applicable Standard Operating Procedures (SOP). There are also problems from the owner of the building itself that needs repairs and supervision from the relevant apparatus